2000
DOI: 10.1161/01.cir.101.4.439
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Mitochondrial ATP-Dependent Potassium Channels by Nitric Oxide

Abstract: NO directly activates mitoK(ATP) channels and potentiates the ability of diazoxide to open these channels. These results provide novel mechanistic links between NO-induced cardioprotection and mitoK(ATP) channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
188
3
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(200 citation statements)
references
References 29 publications
8
188
3
1
Order By: Relevance
“…Indeed, several proteins involved in Ca 2+ and redox signaling are known to be modified by S-nitrosation, including L-type Ca 2+ channels [77], ryanodine receptors [78], thioredoxin [79] hemoglobin [80], mitochondrial K + ATP channels [81,82], TRP channels [83], and caspases [26]. The relative importance of complex I as a mediator of the cardioprotective effects of NO • remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several proteins involved in Ca 2+ and redox signaling are known to be modified by S-nitrosation, including L-type Ca 2+ channels [77], ryanodine receptors [78], thioredoxin [79] hemoglobin [80], mitochondrial K + ATP channels [81,82], TRP channels [83], and caspases [26]. The relative importance of complex I as a mediator of the cardioprotective effects of NO • remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The origin of these protective reactive species can be many, including mitochondria, in which K þ ATP (mK ATP ) channels, which are considered targets of protective cascades (14,142,161,168,201), may play a pivotal role. In fact, it has been suggested that mK ATP channel activation leads to alkalinization of the mitochondrial matrix and generation of ROS=RNS with a protective signaling role (33,142,168,201).…”
Section: Interaction Between Redox Environment and Cardioprotective Pmentioning
confidence: 99%
“…In fact, it has been suggested that mK ATP channel activation leads to alkalinization of the mitochondrial matrix and generation of ROS=RNS with a protective signaling role (33,142,168,201). It has also been suggested that NO donors activate mK ATP channels in rabbit ventricular myocytes and potentiate the protective effect of mK ATP opener diazoxide (168).…”
Section: Interaction Between Redox Environment and Cardioprotective Pmentioning
confidence: 99%
“…In addition, a recent study in rabbits has shown that early translocation of protein kinase C, especially the ␣, , and ␦ isoforms to the membranous fractions, may play an essential role in sildenafil-induced cardioprotection (16). Based on these studies (13)(14)(15)(16), we postulated that sildenafil triggers signaling cascade that involves the activation of protein kinase C, the generation of NO, and the accumulation of cGMP in the myocardium through inducible and endothelial nitric-oxide synthase (iNOS and eNOS), thereby leading to cardioprotection via opening of mitochondrial ATP-sensitive potassium channels (17)(18)(19) .…”
mentioning
confidence: 99%